Delivery Systems to Enhance Bioaccessibility and Bioavailability of Bioactive Factors: Structure, Property, and Food Applications - Yaqiong Zhang; Xin Jia (Foods, 2023)
Incorporating bioactive factors to strengthen food nutrition is important for functional food development [...]